Patients' self-reported measures of oral health: a validation study on basis of oral health questions used in a large multi-country survey for populations aged 50+ - Sekundo, Caroline; Stock, Christian; Listl, Stefan (Gerodontology, 2019)
Objective To assess the validity of patient self-reported oral health measures as used in a large multi-country survey for populations aged 50+. Background Information on people's oral health status is important for assessing oral health needs within populations. However, clinical examination is not always possible. Patient self-reported measures may provide an alternative when time and other resources are scarce. Materials and methods Using oral health items from the Survey of Health, Ageing and Retirement in Europe (SHARE), self-reported measures were collected from 186 patients receiving treatment at Heidelberg University Hospital. Self-reports were compared with subsequent clinical examinations. Analyses were conducted for patients of all age groups and separately for patients aged 50+ (analogous to the SHARE study population). Diagnostic accuracy, agreement and correlation of patient-reported information were examined using descriptive statistics and Bland-Altman plots. Results Patient-reported presence or absence of a full tooth count was closely related to clinical measurement, both for all age groups (sensitivity: 93%; specificity: 92%) and persons aged 50+ (sensitivity: 100% specificity: 94%). Bland-Altman plots indicate good agreement between patient- and clinical reports of the number of teeth at age 50+ (Concordance Correlation Coefficient = 0.95). Discriminatory power of patient-reporting was good regarding presence vs absence of artificial teeth, but less robust regarding partial vs full replacement of missing teeth. Conclusion Patient self-evaluations provide reasonable estimates of clinical measures and appear sufficiently accurate for examining variations in the number of teeth, including among populations aged 50+. However, patient reports of the extent of replacement of missing teeth may not constitute reliable reflections of clinical conditions.